Pengujian Water Hammer Pada Berbagai Berbagai Tekanan Hidrostatis - Idul, Idul; Mangalla, Lukas Kano; Barata, La Ode Ahmad (Teknik Mesin Universitas Halu Oleo, 2021)
Fluids are an important aspect of everyday life. A fluid is a substance that can flow. In the pipeline, the problem that often occurs is the occurrence of fluctuations in water pressure due to the sudden closure of the water flow. The purpose of this research is to study the effect of water hammer on pressure fluctuations at various heights, and to determine the phenomenon of water hammer on flow in pipes at various water surface elevations. The research method was carried out by testing the water hammer at hydrostatic pressure with a water level of 2.40 m, 2.60 m, and 2.80 m. The test is carried out in conditions just after the valve is closed. From the results obtained for the height of h 2.40 m, 2.60 m and 2.80 m have a discharge of 0.000543 m3/s, 0.000558 m3/s and 0.000568 m3/s. pressure fluctuations in the pipe for a height of 2.40 (m), with a duration of fluctuation of 12.48 (s), for a height of 2.60, (m) with a duration of fluctuation of 14.37 (s), and at a height of 2.80 (m) fluctuated by 17.56 (s). The higher the water level, the higher the fluctuations produced. The occurrence of altitude fluctuations is caused by the closing of the valve at the end of the pipe so that the water increases and after experiencing an increase there is a decrease in height until it is constant